Management and Level of Asian small-clawed otter (Aonyx cinereus Illinger, 1815) as Display Animal in Indonesia Conservation Institution - Ulfa Hansri Ar Rasyid; Burhanuddin Masyud; Arzyana Sunkar (Media Konservasi, 2017)
Education and breeding become main reasons for asian small-clawed otter placement as display animal in zoo. Proper management is needed to maintain asian small-clawed otter welfare. This research objectives were to examine and assess asian small-clawed otter welfare in three Indonesia zoos. The study was conducted from December 2016 to February 2017 in Bandung Zoo, Ragunan Zoo and Ocean Dream Samudra Ancol. The methods of this research were literature review, interview and field observation. Data were analyzed using the suitability of management and animal welfare assessment. The result showed that there were three main management activities conducted at the three study locations, i.e., nutrition, housing, and health management. Bandung Zoo achieved the lowest score of asian small-clawed otter welfare (45,24%) compared to Ragunan Zoo (62,24%) and Ocean Dream Samudra (65,90%). Asian small-clawed otter welfare in three institutions were relatively low to fair category, this was due to the unfilled quality of food and water i.e., the type, amount, feeding frequency, diet and preparing of food; the unavailability of suitable and favorable environmental conditions; the care facilities provided could not ensure the health of animal; the appearance of abnormal behavior that affected the growth and breeding of animal; and animal had no freedom to behave as in their natural habitat. Keywords: animal display, animal welfare, Asian small-clawed otter, zoo